The effect of non-metallic dopants addition on the properties of lead-free solders – a review / Nurathiqah Baharuddin - Baharuddin, Nurathiqah (2022)
The objective of this review is to study the effect of non-metallic dopants addition on the properties of lead-free solder. These properties are important as it portray a good solder that can be used in electronic devices. Variety of lead-free solder and non-metallic dopants are being analyzed by using previous study by other researchers. This review is focusing on the influence of variety non-metallic dopants in the melting temperature, intermetallic, solder joint strength and electrical properties, as full understanding of the process that determine a good and reliable solder, which can replace the hazardous lead solder. At the end of this review, the effects of non-metallic dopants addition are explained which have affect the properties of lead-free solder.